2007
DOI: 10.1051/ebr:2007046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of crossability between triticale (XTriticosecaleWittmack) and common wheat, durum wheat and rye

Abstract: Development of transgenic triticale as a platform for novel bio-industrial products is predicated on an environmental biosafety assessment that quantifies the potential risks associated with its release. Pollen-mediated gene flow to related species and conventional triticale varieties is one pathway for transgene movement. A tier 1 quantification of triticale hybridization was conducted by emasculating and hand pollinating flowers under greenhouse conditions. Approximately 2000 manual pollinations were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
0
23
1
1
Order By: Relevance
“…In the present study, crosses conducted among maintainers of triticale and rye showed low efficiency. This contrasts with studies of other authors (Tarkowski & Otl -owska, 1968;Guedes-Pinto et al, 2001;Hills et al, 2007), who obtained higher seed set, although crossability in these studies depended on the parental genotype and environmental conditions (Guedes-Pinto et al, 2001).…”
Section: Discussioncontrasting
confidence: 84%
“…In the present study, crosses conducted among maintainers of triticale and rye showed low efficiency. This contrasts with studies of other authors (Tarkowski & Otl -owska, 1968;Guedes-Pinto et al, 2001;Hills et al, 2007), who obtained higher seed set, although crossability in these studies depended on the parental genotype and environmental conditions (Guedes-Pinto et al, 2001).…”
Section: Discussioncontrasting
confidence: 84%
“…Several markers have been used in other crops to detect pollen-mediated gene flow in donor-receptor experiments including molecular markers based on quantitative PCR (Weekes et al, 2005(Weekes et al, , 2007Pla et al, 2006;Weber et al, 2007) or micro-satellite markers (Chaix et al, 2003;Dje et al, 2004;Isagi et al, 2004). Other techniques like green fluorescent protein (Halfhill et al, 2003) and blue aleurone seed color in wheat (Hanson et al, 2005) and triticale (Hills et al, 2007) ) (Kenaschuk and Rashid, 1994) and low ALA 'Solin' (o3% ALA) cultivars have been developed (Dribnenki et al, 2003). Two independently inherited genes, LuFA-D3A and LuFAD3B control the ALA trait in flax (Vrinten et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These examples underscore the need for detailed environmental risk assessments before release of new genetically engineered crops. Genetically engineered triticale (tribe Triticeae, = Poaceae) is being examined for a range of uses, including bioproducts (CTBI, 2008;Hills et al, 2007;Zimny et al, 1995). Relatively new to agriculture, triticale is an intergeneric hybrid between wheat and cultivated rye (Secale cereale L.).…”
Section: Potential Hybridization Of Genetically Engineered Triticale mentioning
confidence: 99%